2020
DOI: 10.2196/16831
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App to Help People With Chronic Illness Reflect on Their Strengths: Formative Evaluation and Usability Testing

Abstract: Background Supporting patient engagement and empowerment is increasingly seen as essential in providing person-centered health care to people with chronic illness. Mobile apps helping patients reflect on their concerns as preparation for consultations with their health care providers can have beneficial effects on the consultation quality. However, apps focusing on empowerment and personal strengths are still scarce. Objective This study aimed to (1) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…However, when Apps with PROMs are commonly used, some patients will be unfamiliar with scores depicted to them requiring their education [ 4 ]. More educational content has recently also been identified for the next iteration step of an App developed by Kristjansdottir et al [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when Apps with PROMs are commonly used, some patients will be unfamiliar with scores depicted to them requiring their education [ 4 ]. More educational content has recently also been identified for the next iteration step of an App developed by Kristjansdottir et al [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, there have been several studies related to the usability of medical mobile applications. For patients with rheumatic diseases, Kristjansdottir et al [ 17 ] analyzed the usability of the mobile application among 12 rheumatic patients and they found that the satisfaction point was 86.3/100. Islam et al [ 18 ] explored the usability issues of the mHealth application, and the study showed that the services and functions were acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al [ 18 ] explored the usability issues of the mHealth application, and the study showed that the services and functions were acceptable. Kuhns et al [ 16 , 17 , 18 , 19 ] exposed the usability of a mobile application for HIV prevention for transgender women, and they found the satisfaction score of the application to be 4.59/5. Moreover, the participants suggested enhancing application engagement by adding user experience and user interface for attracting new users [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some explained that these types of strengths are out of their control and are thus elements they cannot impact or work on acquiring. Addressing this type of issue, Kristjánsdóttir et al [ 84 ] grouped strengths into 4 categories (ie, personal strengths, strategies, resources in the environment, joy, and meaning), giving the users the choice of which category of strengths to assess. For MyStrengths, it might be that giving users the option to hide unwanted strengths could reduce the negative experiences from being reminded of strengths that are, for instance, out of reach.…”
Section: Discussionmentioning
confidence: 99%